Activation of Melanocortin-4 Receptor Inhibits Both Neuroinflammation Induced by Early Exposure to Ethanol and Subsequent Voluntary Alcohol Intake in Adulthood in Animal Models: Is BDNF the Key Mediator? - Flores-Bastías, Osvaldo; Adriasola-Carrasco, Alfredo; Karahanian, Eduardo (Frontiers in Cellular Neuroscience, 2020)
The concept that neuroinflammation induced by excessive alcohol intake in adolescence triggers brain mechanisms that perpetuate consumption has strengthened in recent years. The melanocortin system -melanocortin 4 receptor (MC4R) and its ligand α-melanocyte-stimulating hormone (α-MSH)- has been implicated both in modulation of alcohol consumption and in ethanol-induced neuroinflammation decrease. Chronic alcohol consumption in adolescent rats causes a decrease in α-MSH release by the hypothalamus, while the administration of synthetic agonists of MC4R causes a decrease in neuroinflammation, and a decrease in voluntary alcohol consumption. However, the mechanism that connects the activation of MC4R with the decrease of both neuroinflammation and voluntary alcohol consumption has not been elucidated. Brain-derived neurotrophic factor (BDNF) has been implicated in alcohol drinking behavior, dependence and withdrawal, and its levels are reduced in alcoholics. Deficiencies in BDNF levels increased ethanol self-administration in rats. Further, BDNF triggers important anti-inflammatory effects in the brain, and this could be one of the mechanisms by which BDNF reduces chronic alcohol intake. Interestingly, MC4R signaling induces BDNF expression through the activation of the cAMP-responsive element-binding protein (CREB). We hypothesize that ethanol exposure during adolescence decreases the expression of α-MSH and hence MC4R signaling in the hippocampus, leading to a lower BDNF activity that causes dramatical changes in the brain (e.g. neuroinflammation and decreased neurogenesis) that predispose to maintain alcohol abuse until adulthood. The activation of MC4R either by α-MSH or by synthetic agonist peptides can induce the expression of BDNF, which would trigger several processes that lead to lower alcohol consumption.